2010
DOI: 10.2174/156802610791111551
|View full text |Cite
|
Sign up to set email alerts
|

Review of 5-HT4R Ligands: State of Art and Clinical Applications

Abstract: This article reviews the medicinal implications of 5-HT(4)R in the peripheral and central nervous systems, based on data from two hundred bibliographic references. An exhaustive compilation of molecules reported to be antagonists or agonists for 5-HT(4)R is presented, including chemical structures, binding properties and pharmacological profiles. In the last part of the review, some key concepts concerning structure-activity relationships are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 114 publications
(154 reference statements)
1
10
0
Order By: Relevance
“…However, there are inconsistencies in the generalizability of 5-HT 1B/2C agonists to substitute for ethanol across sex and species, as RU 24969 only partially substituted for ethanol in female rats [36] and mCPP did not generalize from ethanol in mice [64]. Refinement of receptor ligands with increased selectivity for 5-HT 1 and 5-HT 2 receptor isoforms (e.g., [69, 70]) coupled with a rapid expansion of novel ligand development for 5-HT 4 receptors, which also function to regulate neurotransmission in conjunction with 5-HT 1 and 5-HT 2 receptors [71, 72], should prompt a fresh look at the involvement of metabotropic 5-HT receptors in modulating the discriminative stimulus effects of ethanol.…”
Section: 1 Rodentsmentioning
confidence: 99%
“…However, there are inconsistencies in the generalizability of 5-HT 1B/2C agonists to substitute for ethanol across sex and species, as RU 24969 only partially substituted for ethanol in female rats [36] and mCPP did not generalize from ethanol in mice [64]. Refinement of receptor ligands with increased selectivity for 5-HT 1 and 5-HT 2 receptor isoforms (e.g., [69, 70]) coupled with a rapid expansion of novel ligand development for 5-HT 4 receptors, which also function to regulate neurotransmission in conjunction with 5-HT 1 and 5-HT 2 receptors [71, 72], should prompt a fresh look at the involvement of metabotropic 5-HT receptors in modulating the discriminative stimulus effects of ethanol.…”
Section: 1 Rodentsmentioning
confidence: 99%
“…DISCUSSION 5-HT4R is a serotonin receptor subtype that can be expressed and purified to reasonable purity and homogeneity. In addition, the pharmacokinetics of its ligand interactions have been well studied (37) making it an excellent model system for exploring GPCR structure-function. In this study, we analyzed the ligand binding properties of a physiologically active form of 5-HT4R that was stable under various experimental conditions.…”
Section: Table I Rates Of 5-ht4r Peptide Oxidation Calculated From Ramentioning
confidence: 99%
“…Previous results have shown that some 5-HT 4 R ligands bearing bulky aromatic group bonded to the lateral chain can exhibit high affinities. 3 Accordingly, compounds 11C and 11d were synthesized. Despite the introduction of the bulky iodoaryl group, the iodinated 4-fluorobenzonaphthyridine 11d was found to exhibit high affinity for both guinea pig 5-HT 4 R (Ki = 2.5 nM) and human 5-HT 4 R (Ki = 0.23 nM) in the similar order of magnitude as compound 4v .…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Pharmacological investigations coupled to the discovery of ligands exhibiting high affinity and selectivity for 5-HT 4 Rs have led to know their anatomical distribution and functional roles. 5-HT 4 Rs are found in the peripheral system, where they are implicated in gastrointestinal disorders 5 and heart failures 6 .…”
Section: Introductionmentioning
confidence: 99%